This Is the End: Regulation of Rab7 Nucleotide Binding in Endolysosomal Trafficking and Autophagy - Stroupe, Christopher (Frontiers in Cell and Developmental Biology, 2018)
Rab7 – or in yeast, Ypt7p – governs membrane trafficking in the late endocytic and autophagic pathways. Rab7 also regulates mitochondrion-lysosome contacts, the sites of mitochondrial fission. Like all Rab GTPases, Rab7 cycles between an “active” GTP-bound form that binds downstream effectors – e.g., the HOPS and retromer complexes and the dynactin-binding Rab-interacting lysosomal protein (RILP) – and an “inactive” GDP-bound form that cannot bind effectors. Accessory proteins regulate the nucleotide binding state of Rab7: guanine nucleotide exchange factors (GEFs) stimulate exchange of bound GDP for GTP, resulting in Rab7 activation, whereas GTPase activating proteins (GAPs) boost Rab7’s GTP hydrolysis activity, thereby inactivating Rab7. This review will discuss the GEF and GAPs that control Rab7 nucleotide binding, and thus regulate Rab7’s activity in endolysosomal trafficking and autophagy. It will also consider how bacterial pathogens manipulate Rab7 nucleotide binding to support intracellular invasion and immune evasion.